Maternal anxiety and its correlation with pain experience during chorion villus sampling and amniocentesis - Klages, Katharina; Elsässer, Michael; Scharf, Alexander (Journal of pain research, 2017)
Maternal anxiety and its correlation with pain experience during chorion villus sampling and amniocentesis Katharina Klages,1,2 Sudip Kundu,1 Joachim Erlenwein,3 Michael Elsaesser,4 Peter Hillemanns,1 Alexander Scharf,4 Ismini Staboulidou1 1Department of Gynecology and Obstetrics, Hanover Medical School, Hanover, 2Department of Gynecology and Obstetrics, Diakovere Friederikenstift Hanover, Hanover, 3Department of Anesthesiology, University of Goettingen, Pain Clinic, Goettingen, 4Department of Gynecology and Obstetrics, University of Heidelberg, Heidelberg, Germany Purpose: Invasive prenatal diagnostic procedures, such as chorion villus sampling (CVS) and amniocentesis (AC), are routinely performed to exclude or diagnose fetal chromosomal abnormalities. The aim of this study was to investigate anxiety-dependent pain experience during CVS and AC and the potential factors that increase anxiety and pain levels. Patients and methods: During a 2-year period, women undergoing invasive procedures in three specialist centers were asked to participate in the study. Anxiety was evaluated before the procedure using the Spielberger State-Trait-Anxiety-Inventory, and pain was evaluated directly after the procedure using a verbal rating scale. Results: Among the women, 348/480 (73%) underwent AC, while 131/480 (27%) underwent CVS. There was a significant correlation between state and trait anxiety (p